Trastuzumab holds potential to accelerate spontaneous sensory reinnervation after free flap breast reconstruction: a proof of concept - Leskovar Jana; Petrovečki Marko; Bulić Krešimir (Innovative Surgical Sciences)
Breast sensation following autologous breast reconstruction impacts patients’ quality of life. Although spontaneous reinnervation in free flaps was documented by many authors, there are efforts to further improve restoration of breast sensation. Interestingly, animal studies indicated that trastuzumab has several beneficial effects on transected peripheral nerves. Our aim was to compare spontaneous sensory recovery after free TRAM flap breast reconstruction between patients who were and were not treated with trastuzumab.